Detection of Short-Circuit Location in Distribution Mains Line within Functions of Micro-Processor Current Protection - F. A. Romaniuk; A. A. Tishechkin; O. A. Gurjanchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a method for improvement of micro-processor current protection lines that permits to expand a zone of instantaneous short-circuit cut-off  and decrease a number of discriminating elements. In order to reach this purpose the paper proposes additionally to determine a distance up to the short circuit location within functions of the lines concerned. A distance principle for determination of a distance up to the damage place can be laid down in the basis for сalculation of short-circuit location while using an algorithm of orthogonal components or a 3-counting algorithm. The first mentioned algorithm is characterized by higher accuracy but it is sensitive to frequency changes. The 3-counting algorithm is practically insensitive to frequency changes but it is less accurate. Altogether each of the considered algorithms is operational and ensures obtaining of the required information for efficient realization of functions for detection of damage location.The given propositions can be used while developing algorithms for operation of micro-processor current directed protections of distribution mains lines.